(untitled) (Bridging Cultures, 2023)
In this paper we deepen our previous analysis (Pacagnini, 2016; 2017; 2020) of linguistic features considered relevant to assess fluency in an oral exam of Spanish proficiency (more specifically, the Certificate of Spanish: Language and Use -CELU-, granted by the Argentine Interuniversity Consortium for the Teaching and Testing of Spanish as a Second and Foreign Language). With this aim, we continue to survey those aspects that are usually considered by the evaluators in the analytical assessment sheets and by the interlocutors in the holistic ones, comparing this with the justifications given by the evaluators when determining certain aspects as indicators of fluency in a survey conducted afterwards. At this stage of our research, we try to determine the factors that are taken into account when pointing to a non-native speaker as “fluent”, and we expand our study on the features considered by the CELU evaluators, in order to propose improvements in assessment rubrics.